Hubungan Tingkat Ketergantungan Activity Of Daily Living (ADL) Terhadap Depresi Pada Pasien Post Stroke Di RSUD Kabupaten Bekasi - Nenden Riffa Mardiani; Naziyah Naziyah; Rizki Hidayat (Universitas Malahayati Lampung, 2022)
ABSTRACT The high prevalence of stroke is a trigger for death and a trigger for disability globally, including Indonesia. Hemiparesis arising from impaired brain function can limit the patient's independence to carry out activities of daily living (ADL) such as eating, drinking, bathing and changing clothes, thus requiring the help of others. Facing poor mobility can lead to post-stroke depression. To determine the relationship between activity of daily living (ADL) dependence on depression in post-stroke patients. This research uses a descriptive correlation method with a cross sectional approach. The sample in this study amounted to 61 respondents of post-stroke patients in Bekasi District Hospital. The sampling technique used was purposive sampling. The research instrument consisted of a Barthel Index and Depression Anxiety Stress Scales (DASS 42) questionnaire. This questionnaire is a standard questionnaire that has been tested for validity and reliability. The data were analyzed using the Spearman rank test to determine the relationship between dependence of activity of daily living (ADL) on depression. There is a relationship between the level of dependence of activity of daily living (ADL) on depression with a p value of 0.000 (0.05) with an r value of 0.824. There is a relationship between the level of dependence of activity of daily living (ADL) on depression in post-stroke patients at the Bekasi District Hospital. The higher the level of dependence on activity of daily living (ADL), the higher the level of depression. Keywords : Post Stroke, Activity of daily living (ADL), Depression ABSTRAK Prevalensi penyakit stroke yang masih tinggi menjadi pemicu kematian dan pemicu kecacatan secara global termasuk Indonesia. Hemiparesis yang timbul akibat gangguan fungsi otak dapat membatasi kemandirian pasien untuk melakukan activity of daily living (ADL) seperti makan, minum, mandi dan berganti pakaian, sehingga membutuhkan bantuan orang lain. Menghadapi mobilitas yang buruk dapat menimbulkan terjadi depresi post stroke. Tujuan untuk mengetahui hubungan tingkat ketergantungan activity of daily living (ADL) terhadap depresi pada pasien post stroke. Penelitian menggunakan jenis metode deskriptif korelasi dengan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 61 responden pasien post stroke di RSUD Kabupaten Bekasi. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen penelitian terdiri dari kuesioner Indeks Barthel dan Depression Anxiety Stress Scales (DASS 42). Kuesioner ini merupakan kuesioner baku yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan uji spearman rank untuk mengetahui hubungan tingkat ketergantungan activity of daily living (ADL) terhadap depresi. Adanya hubungan tingkat ketergantungan activity of daily living (ADL) terhadap depresi dengan nilai p value 0,000 α (0,05) dengan nilai r hitung 0,824. Ada hubungan antara tingkat ketergantungan activity of daily living (ADL) terhadap depresi pada pasien post stroke di RSUD Kabupaten Bekasi. Kata kunci: Post Stroke, Activity of daily living (ADL), Depresi